Effectiveness of Red Bean (Phaseolus vulgaris L.) Processing on Improving Hemoglobin in Anemic Pregnant Women - mayang citra hariati; Ika Nur Saputri; Pitriani .; Rani Cahya (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Anemia during pregnancy is still a common health problem and can have serious impacts on the health of both the mother and the fetus. Iron deficiency is the main cause, thus effective prevention and management efforts are needed, either through supplementation or the intake of nutritious foods rich in iron. One natural food ingredient that has the potential to increase hemoglobin levels is red beans (Phaseolus vulgaris). The purpose of this study is to determine the effectiveness of red bean preparations in increasing hemoglobin in pregnant women experiencing anemia at the Mars Clinic. The study used a Quasi-Experimental method with a One Group Pre Test Post Test approach. By using a total sampling technique, 17 respondents were obtained. The results of the Wilcoxon statistical test showed a p-value of 0.001 (p < 0.05), which means there is a significant effect of giving red bean porridge on the increase of hemoglobin levels in pregnant women. It is recommended that healthcare workers, especially midwives, promote the prevention and management of anemia by utilizing foods such as red beans.